Identifying, Assessing, and Treating Early Onset Schizophrenia at School - Li, Huijun; Pearrow, Melissa; Jimerson, Shane R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
By itself or in combination with an affective disorder, early onset schizophrenia (EOS) $1 (Bthe onset of symptoms before 18 years of age $1 (Bcan create severe deficits in young people$1 (Bs academic performance, family and peer relationships, and even the ability to acquire new skills. The relative rarity of the condition, meanwhile, can leave school personnel unsure of how to meet $1 (Bor even recognize $1 (Bstudent needs. Identifying, Assessing, and Treating Early Onset Schizophrenia at School emphasizes the importance of providing teachers and students alike with the support needed to enhance academic performance and improve social skills of children and adolescents with EOS within educational settings. In addition, its evidence-based framework enables school professionals to achieve greater confidence and accuracy in identifying students with EOS and provide appropriate services, both in special education and general classes. In this authoritative and accessible volume, experts offer the most salient information on early onset schizophrenia, including: Contributing factors and risk factors. Prevalence and epidemiology. Screening and assessment procedures. Guidelines for determining eligibility for special education programs under IDEIA and Section 504. Latest findings on school-based and off-campus interventions for EOS. A useful resource appendix. Identifying, Assessing, and Treating Early Onset Schizophrenia at School gives school psychologists and allied education professionals both a practical understanding of this disabling condition and the most up-to-date strategies for providing earlier and effective interventions.s
Causes -- Prevalence, Incidence, and Associated Conditions -- Case Finding and Screening -- Diagnostic Assessment -- Psychoeducational Assessment -- Treatment -- Erratum to: Identifying, Assessing, and Treating Early Onset Schizophrenia at School.
Keywords: Philosophy (General).; Applied psychology; Developmental psychology; Psychology; Child and School Psychology; Education (general).; Psychotherapy and Counseling; Developmental Psychology